Study of tactics and personal security measures of the dialogue police during the protection of public order at mass events (Law and Safety, 2022)
Further reform of law enforcement activities in Ukraine is, of course, absolutely necessary and requires constant attention from the leadership of the Ministry of Internal Affairs, the National Police and the services and units involved in this activity. The scientific approach and the definition of new directions and technologies are impossible without the use of research studies of the scientific and pedagogical staff of higher education institutions with specific learning conditions. The article analyzes the work of the dialogue police, identifies directions for improving their activities in terms of serving at mass events. Dialogue police is one of the main innovations in the proposed system of public order protection, which is implemented in the law enforcement activities of Ukraine as a “Scandinavian model”.The main tactical tasks of the dialogue police have been formulated, which include communication tactics and tactical skills. Based on the expert survey of police officers from different units, a list of problematic issues has been identified and directions for further research have been formulated. The factors that affect the effectiveness of the dialogue police during the service have been considered and analyzed, which made it possible to adjust the tactics of actions and personal security measures of the personnel. The tactics and personal security measures of the dialogue police are based on the basic principles of the Scandinavian model, the capabilities of the National Police, the theory of the crowd, the features of mass events, the differentiation of dangers and the “tree of events”.The actions and location of the dialogue police personnel have been proposed depending on the color of the “barometer of the situation” (green, yellow, red), the location in relation to other units of the National Police has been established. The conclusions and recommendations have been given, on the basis of which it is possible to reduce the level of injuries among the personnel of the dialogue police during the service at mass events and to increase their effectiveness; they can be used during the preparation of police officers for service and targeted instruction.
Keywords: National police; dialogue police; protection of public order; Scandinavian model; mass events; tactics; personal security measures.